The origin and tectonic evolution of the Annieopsquotch ophiolite belt, Newfoundland Appalachians - Lissenberg, Cornelis Johannes (University of Ottawa (Canada), 2005)
The Annieopsquotch Accretionary Tract comprises a series of arc-back arc complexes and ophiolites that formed in lapetus Ocean and were accreted to the composite Laurentian margin, providing a unique view of tectonic processes operating during the Ordovician Taconic orogeny. The Annieopsquotch ophiolite belt, the oldest and structurally highest complex, preserves three magmatic episodes, and formed during initiation of west-directed subduction. It thus records the formation of the subduction zone that was responsible for formation of the units preserved in the Annieopsquotch Accretionary Tract. The Annieopsquotch ophiolite belt was accreted to the Laurentian margin prior to 470 Ma along the sinistral-oblique Lloyds River Fault Zone. The Lloyds River Fault Zone was intruded syn-kinematically by two plutonic suites (464-459 Ma), which triggered renewed deformation at high temperatures, illustrating that a positive feedback between deformation and magmatism facilitates the transfer of oceanic complexes to continental margins. Age constraints indicate that the majority of the Annieopsquotch Accretionary Tract was accreted 5 to 10 Ma after formation of the units, illustrating that complexities of accretionary tectonics in lapetus were similar to those in Mesozoic to recent accretionary orogens. In contrast to other accretionary orogens, the role of fore-arc accretion was limited, whereas recycled continental basement played an important role. Syn-kinematic plutons tapped not only a sub-arc mantle source, but also a lithospheric mantle and crustal source, leading to isotopically evolved signatures. The majority of the gabbro zone of the Annieopsquotch ophiolite is composed of gabbroic cumulates with paleohorizontal intrusive contacts. These contacts have finer grain sizes and comb structures (crescumulates), suggesting they are sills. The parental magmas of cumulates in the sills had compositions very similar to the overlying sheeted dykes and basalts, and generally become more evolved up-section, indicating that magma evolution in the Annieopsquotch ophiolite was dominated by fractionation in lower crustal conduits. The parental magmas of the gabbros, sheeted dykes, and basalts preserve a similar, wide range of compositions, indicating that aggregation, homogenization, and fractionation in an axial melt lens was inefficient. Lower crustal accretion was thus dominated by intrusion of melts from below, rather than remobilization of cumulates from above.